ҚЫЛМЫСТЫҚ ІС ЖҮРГІЗУДЕГІ АЗАМАТТЫҚ ТАЛАП: НЕГІЗДЕРІ МЕН АЛҒЫШАРТТАРЫ (Journal of actual problems of jurisprudence, 2019)
In article it is considered the bases and civil suit preconditions in criminal trial.